"Mycobacterium avium subsp. hominissuis" in neck lymph nodes of children and their environment examined by culture and triplex quantitative real-time PCR - Kaevska, Marija; Slana, Iva; Kralik, Petr; Reischl, Udo; Orosova, Jaroslava; Holcikova, Alena; Pavlik, Ivo (Journal of clinical microbiology, 2011)
"Mycobacterium avium subsp. hominissuis" often causes cervical lymphadenitis in children; its prompt and accurate identification enables adequate therapy, tracing, and prevention. The aims of this study were to determine the causative agent of lymphadenitis using culture, PCR, and triplex quantitative real-time PCR (qPCR) methods with DNA directly isolated from tissue, as well as to identify possible sources of infection from the environment. We confirmed the diagnoses by detecting M. avium subsp. hominissuis using qPCR with DNA directly isolated from lymph node biopsy specimens of two patients. In order to trace the source of infection from the environment, a method of DNA isolation from soil and other environmental samples, such as dust, cobwebs, and compost, was developed. The triplex qPCR examination revealed the presence of M. avium subsp. hominissuis in a high proportion of the environmental samples (42.8% in the first patient's house and 47.6% in the second patient's house). Both patients were also exposed to M. avium subsp. avium, which was present due to the breeding of infected domestic hens. The high infectious dose of M. avium subsp. hominissuis or the increased susceptibility of humans to M. avium subsp. hominissuis compared to M. avium subsp. avium could be the reason why the children were infected with M. avium subsp. hominissuis.
Keywords: polymerázová řetězová reakce; Polymerase Chain Reaction; polymorfismus délky restrikčních fragmentů; mužské pohlaví; Bacteriological Techniques; bakteriologické techniky; dítě; Child; Environmental Microbiology; molekulární typizace; Child, Preschool; Molecular Typing; ženské pohlaví; Neck; Humans; předškolní dítě; tuberkulóza lymfatických uzlin; krk; mikrobiologie životního prostředí; Polymorphism, Restriction Fragment Length; Tuberculosis, Lymph Node; Mycobacterium avium; Female; lidé; Male